Bungled Pronunciation of English in Colleges of Punjab, Pakistan: A Survey Along with its Ramifications - Ahmed, Akeel (International Journal of Engineering and Technology, 2018)
The prime and predominant objective of this study is to investigate and analyze the botched pronunciation of English language words prevalent in public and private sector colleges of Punjab, Pakistan. We have discussed that, what are the key factors which are responsible for such botched and poor pronunciation. The paper has surfaced the bungled pronunciation got through an oral questionnaire. The paper has identified the major pitfalls embedded in English language pronunciation while pointing out why it is happening and where the problem lies. A comparative study regarding public colleges of those countries where English is secondary language viz. India, Bangladesh and Sri Lanka. Students of different subjects and teachers of different subjects having teaching experience of several level have been taken on board. Altogether 30 govt. in-service public sector college teachers and 40 teachers from private sector colleges responded to the questionnaire; and 117 students from private and public sector colleges tendered responses. The study has underpinned the English language skill of the teachers by pinpointing that what weightage pronunciations bears in English language skill. Â Â